Development of the function of autobiographical memories evoked by odor scale for older Japanese people - Yamamoto, Kohsuke; Yokomitsu, Kengo; Kobayashi, Takefumi (Frontiers in Psychology, 2022)
Odor-evoked autobiographical memory and related psychological changes have been evaluated based on several factors, such as emotionality, clarity, and re-experience. We developed the Function of Autobiographical Memory cued by Odor Scale (FAMOS) for older Japanese people as a new method for comprehensively evaluating the functions of odor-evoked autobiographical memory. We used the diary method; participants were instructed to record the contents of everyday involuntary autobiographical memories triggered by odor and complete the FAMOS. In Study 1, 600 older adults were surveyed to select items for the FAMOS and examine the factor structure. We obtained four factors of “Evoking Positive Emotion,” “identity,” “Facilitating communication,” and “Coping with negative emotion.” Sufficient reliability was demonstrated. In Study 2, the FAMOS’s validity was examined in 600 older adults. We found significant correlations with the affective valence of odors, the Odor Evoked Autobiographical Memory Questionnaire, and other scales, confirming the validity of the FAMOS. In Study 3, the FAMOS was administered to 600 younger and 600 older adults; generational differences were compared for further validity. Older adults had higher “Evoking Positive Emotion,” “identity,” and “Facilitating communication,” scores on the FAMOS than younger adults, suggesting a fair degree of reliability and validity of the FAMOS.